The use of conjunctions in tamil language essays among secondary students - Bavani Arumugam; Nurul Nazira bt Hamzah; Lau Yoke Lian; Nur Amirah Nadiah binti Mustapa kamal (Penerbit Universiti Malaysia Sabah, 2024)
The aim of the paper was to assess learners’ knowledge on conjunctions, identify the conjunctions used by the learners in essays, and analyse the correlation between the use of conjunctions and the learners’ essays grade. This descriptive research explains the use of conjunctions in essays written by Tamil secondary school students. The researcher used a quantitative method in this research, which involved 48 students in a secondary school in Kuala Kangsar, Perak. The researcher employed two instruments: The first instrument is Multiple-choice questions (MCQ) consist of 40 objective questions on conjunctions and the second instrument is an expository essay test. All the essays were marked holistically based on the Sijil Pelajaran Malaysia (SPM) format by the researcher. The researcher adapted Halliday and Hasan (1976) concept of conjunctions. The findings showed that the students have a better knowledge on additive, adversative and causal conjunctions as compared to temporal conjunctions. Furthermore, additive conjunctions were frequently used 855 (59.8%) times in the students’ essays. It is followed by causal conjunctions 312 (21.8%) times and temporal conjunctions 175 (12.2%) times. Meanwhile, the use of adversative conjunctions was the least frequent at 88 (6.1%) times. Besides, the study also indicated significant correlation between the use of conjunctions and the students’ grade at 0.01 in which the value of p is ≤ 0.05. The implication of this study, Tamil language teachers were able to identify the flaws in the usage of conjunction words, particularly in students’ essays writing. Thus, teachers are made aware of the importance of conjunctions, especially in terms of meaning usage and conjunction functions.